Лікування внутрішньочеревних інфекцій: рекомендації консенсусної конференції WSES (2016) - І. А Кryvoruchko (Клінічна хірургія, 2018)
Лікування внутрішньочеревних інфекцій: рекомендації консенсусної конференції WSES (2016)